Nucleotide– and Mal3-dependent changes in fission yeast microtubules suggest a structural plasticity view of dynamics - Ottilie von Loeffelholz; Neil A. Venables; Douglas Robert Drummond; Miho Katsuki; Robert Cross; Carolyn A. Moores (Nature Communications, 2017)
Microtubules are vital and highly conserved components of the cytoskeleton. Here the authors carry out a structural analysis of fission yeast microtubules in the presence and absence of the microtubule end-binding protein Mal3 that demonstrates structural plasticity amongst microtubule polymers.